Analysis of Mount Jae Tourism Management in Efforts to Increase Village Revenue (Case Study: Sedau Village, Narmada District, West Lombok Regency, 2024) - Sari, Desni Rienendra; Hailuddin, Hailuddin; Sujadi, Sujadi (Westscience Press, 2026)
The purpose of this study is to describe how to analyze the management of the Mount Jae tourist attraction in an effort to increase village original income in Sedau Village, Narmada District, West Lombok Regency. The method used in this study is a qualitative approach. This research was conducted in Sedau Village, Narmada District, West Lombok Regency. The informants in this study were the Village Head, the Head of the Tourism Awareness Group (Pokdarwis), vendors selling at stalls provided at the Mount Jae natural tourist attraction, the local community, and tourism operators visiting the tourist attraction. The data sources used in this study were primary data, namely interviews, and secondary data, namely supporting documents from previous research. The data collection methods used in this study were observation, interviews, and documentation. The results of this study demonstrate the impact of the management of the Mount Jae Nature Tourism Object on increasing village income and improving the community's economy in Sedau Village, Narmada District, West Lombok Regency. This has had a significant impact, especially for unemployed local residents. This impact is achieved through the provision of stalls selling instant food, firewood, and rentals of other tourist facilities such as tents, fishing rods, grills, and boats. Furthermore, the Mount Jae Nature Tourism Object is fully managed by the Tourism Awareness Group (Pokdarwis). Therefore, the Village Government, along with Pokdarwis, encourages unemployed residents to contribute to the development of the Mount Jae Nature Tourism Object. The establishment of this tourist attraction has had a positive impact on increasing community income, enabling them to meet their daily needs and increasing the village's original income to help build village infrastructure and facilities, including the Mount Jae tourist attraction.